2014
DOI: 10.1186/1756-8722-7-39
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of combined platelet-activating factor receptor and epidermal growth factor receptor targeting in ovarian cancer cells

Abstract: BackgroundGenetic alterations, including the overexpression of epidermal growth factor receptor (EGFR), play a crucial role in ovarian carcinogenesis. To date, EGFR targeting has shown limited antitumor effects in ovarian cancer when administered as monotherapy. We previously identified platelet-activating factor receptor (PAFR) as being overexpressed in ovarian cancer and found that its ligand PAF evoked EGFR phosphorylation. To determine whether PAFR targeting can enhance the antitumor efficacy of EGFR inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Phospho-antibody microarray analysis revealed increased EGFR, Src, FAK and Paxillin phosphorylation through PAF in OVCA429 and OVCA432 cells. We also showed that the combined PAFR and EGFR targeting synergistically inhibited the ovarian cancer in vitro and in vivo [28]. However, the mechanisms underlying EGFR phosphorylation through PAF/PAFR in human ovarian cancer have not yet been tested.…”
Section: Introductionmentioning
confidence: 91%
“…Phospho-antibody microarray analysis revealed increased EGFR, Src, FAK and Paxillin phosphorylation through PAF in OVCA429 and OVCA432 cells. We also showed that the combined PAFR and EGFR targeting synergistically inhibited the ovarian cancer in vitro and in vivo [28]. However, the mechanisms underlying EGFR phosphorylation through PAF/PAFR in human ovarian cancer have not yet been tested.…”
Section: Introductionmentioning
confidence: 91%
“…After 12 h, 24 h, 36 h, 48 h or 60 h, CCK-8 was added into each well and cells were incubated for 4 h at 37°C. The absorbance was measured using Enzyme-labelled-meter at 490 nm to calculate cell growth rate (Yu et al, 2014). The experiment was repeated thrice.…”
Section: Determination Of Cell Proliferation Using Cck-8 Assaymentioning
confidence: 99%
“…Approximately 14,030 females succumb every year to ovarian cancer, representing the most common cause of mortality among females with gynecological malignancies (1). Surgical resection and platinum-based combination regimens offer a modest but significant survival advantage in ovarian cancer patients with advanced or metastatic disease, although most patients eventually experience disease progression (2). These data highlight the need to identify new approaches that, along with the current treatments, may assist in bringing about a better outcome for ovarian cancer patients.…”
Section: Introductionmentioning
confidence: 99%